K-POP IDOL STANDARD DAN PRAKTIK KOMODIFIKASI PEKERJA DALAM VIDEO CLIP “IU-CELEBRITY” - Alfitriah, Alfitriah; Alyatalatthaf, Muhammad Dicka Ma'arief (Master of Communication Science Program, Universitas Diponegoro, 2023)
K-pop idols are demanded by agencies and fans based on beauty standards, ideal bodies, how to dress, and self-image. This study aims to describe the forms of K-pop idol standards and the practice of commodifying workers in the video clip “IU – Celebrity.” The Political Economy Theory of Communication from Vincent Mosco is used to see the practice of commodification, using John Fiske's Semiotics analysis method. The results of this study, on: (1) the level of reality, a k-pop idol is required to meet the ideal standards based on the agency as well as fan's wants; (2) representation level, signs at the reality level are transmitted into representational codes such as camera techniques, angles, transitions, video editing, location sets, sound, to special fx; (3) ideological level, it is found that there are capitalistic practices through the commodification of workers towards k-pop idols by the agency in the form of regulating appearance standards, clothing, privacy, and social relations of k-pop idols. This is done by the agency in order to maintain their idol image in accordance with the wishes of fans.